Development of lipase immobilization technique using sago as support for enzymatic esterification and transesterification - Mohtar, Nur Syazwani (2020)
One of the major enzymes produced and used in industries is lipase. Lipases are very versatile catalyst and its applications expand to various industries like oil and fat, dairy, pharmaceutical, detergent, leather, cosmetics and paper. The hitch is enzymes are very sensitive to the change in the environment like temperature and pH. One way to resolve this problem is to immobilize the desired enzyme on a support material. Enzyme immobilization does not only stabilize the enzyme, but it also makes the enzyme suitable to be used for reactions that are sensitive to water because the immobilized enzymes are often in a dry form. This is very important for lipase, as the majority use of lipase in the industry is for ester synthesis and fat modification (transesterification), which only occur in a water-limiting condition. Therefore, the objectives of this research are to develop a simple and effective method to immobilize lipase, using sago as the support, and test the immobilized lipase for esterification and transesterification activity. Sago is the starch extracted from the pith of Metroxylon sagu palm trees. It is deemed suitable as the immobilization support due to its inert nature, stable gel structure and excellent resistance to heat and shear. A thermostable lipase isolated from Geobacillus sp. ARM (ARM lipase) was used in the immobilization study to develop a simple and efficient method to increase the stability of the enzyme. Pure ARM lipase was used to minimize the contaminant that might affect the results of the experiments. Two immobilization techniques using different supports were tested, that is, adsorption on chitosan, amberlite, and layered double hydroxide and entrapment in sago. The highest lipase activity determined was by entrapment of the lipase in gelatinized sago that subsequently spray-dried. The result was supported by the surface area and porosity analysis where the surface area, pore volume, and pore radius decreased by 67%, 50%, and 10%, respectively, when lipase was immobilized into the sago, which indicated that the space had been occupied by the enzyme. This immobilization method has efficiently improved the thermal stability of the enzyme, where the half-life of the enzyme at 80°C was 4 hours, in comparison to the activity of the free enzyme, which dropped instantly from the very first hour. This immobilization method has also successfully preserved the enzyme for a longer shelf-life, which was 9 months at 10°C and 2 weeks at room temperature. The immobilized ARM lipase maintained its optimum temperature for enzyme activity at 70°C and a pH preference from pH7 to pH9. Overall, the results of thermal and pH characterization have shown that the immobilization of lipase on a natural support material such as sago is very promising for industrial use, especially in food manufacturing applications. Two model applications were done to test the lipase immobilized using the newly developed method for synthesis activity in a water-free environment. The immobilized enzyme was used for the synthesis of ethyl oleate by esterification reaction and the synthesis of cocoa butter alternative by transesterification reaction. The usage of dry immobilized lipase is very relevant for these applications. For these experiments, a commercial enzyme, Rhizopus oryzae lipase (ROL), which was immobilized using the newly developed method was used to compare with the ARM lipase. The immobilized ROL showed an outstanding result for the esterification (81.3% at 60°C) compared to ARM lipase (9.9% at 60°C), therefore, it is used for further experiments. The highest conversion of ethyl oleate obtained using the immobilized ROL from this research was 97% with the incubation in a water bath shaker at 40°C and 50°C, 200 rpm shake, for 12 hours, with the substrate ratio of ethanol and oleic acid of 2:1. For the synthesis of cocoa butter alternative using the immobilized ROL in sago, different ratios of palm mid-fraction, olive oil, and stearic acid were used as the substrates. Based on the chemical composition analysis determined by the high performance liquid chromatography (HPLC) and gas chromatographymass spectrometry (GCMS), the product using substrate ratio 1:0:1 has the closest reading to cocoa butter compared to the other ratios, with 21.77% palmitoyl-oleoyl-palmitoyl glycerol, 27.71% palmitoyl-oleoyl-stearoyl glycerol, 13.39% stearoyl-oleoyl-stearoyl glycerol, the total saturated fatty acids of 66.07%, and unsaturated fatty acids of 33.93%. As for the thermal characteristics, the product using substrate ratio 1:1:1 has the closest reading to cocoa butter compared to the other ratios, with the slip melting point of 36.2°C; the solid fat content of 7.73% and 2.02% at 30°C and 40°C respectively. The DSC thermogram showed melting peaks at lower than 37°C (11.56°C and 33.41°C). In a nutshell, the newly developed method of enzyme immobilization using sago as the supporting material is suitable for lipases from a bacterial and a fungal source, for the forward and reverse reactions of lipase.